A co‐creation approach to design the implementation of a multimodal intervention in patients with subjective cognitive decline (PENSA study): Prevention (nonpharmacological) / Multidomain. (7th December 2020) - Forcano, Laura; Soldevila‐Domenech, Natalia; Rodriguez‐Arjona, Maria Dolores; Puig‐Pijoan, Albert; Pizarro, Nieves; Knezevic, Iva; Fauria, Karine; Minguillón, Carolina; Molinuevo, Jose Luis; ,
Abstract: Background: In recent years, there has been a growing concern about the hierarchical relationship between researchers and patients. A change of paradigm has been promoted by recent initiatives supporting an active citizenship involvement in research. The combination of patients' views together with the expertise of clinicians and researchers may lead to a change on how research actions are identified, designed, conducted and disseminated. Following this approach, we introduced a co‐creation action in the intervention design process of the project Prevention of cognitive decline in APOE‐ɛ4 carriers with SCD after epigallocatechin‐gallate and a multimodal intervention (PENSA study). We aimed to assess participants' opinion about the multimodal intervention and its viability, and to identify aspects of improvement. Methods: We performed a qualitative descriptive study in a focus group composed by 10 participants (5 women and 5 men) between 60 and 80 years. Two researchers and a qualitative methodology specialist planned the content of a 2‐hour group session, that was guided by the specialist and audio recorded. Subsequently, an analysis of the thematic content was performed to extract the participants' global comprehension of the phenomenon. Results: The qualitative analysis revealed that participants positively rated the intervention and found it as a useful tool to implement a healthy lifestyle. Facilitators and barriers for the implementation of the multimodal intervention were identified. The former related to the great support received by the health professionals and the opportunity of acquiring reliable knowledge about Alzheimer's disease and its management. The later were mostly related with time availability and a general worry about the return and dissemination of the study results. Moreover, alternatives and changes were proposed to improve the intervention, such as the possibility of adapting the proposed activities to participants' preferences. The research team has implemented a number of actions to adequate the multimodal intervention to the participants needs. Conclusions: Our study shows that co‐creation actions considering patients experience represents a rich source of information for designing effective health interventions. The co‐creation process represents an exercise of public commitment in responsible research and innovation.